Redescription, distribution and mating call of Pristimantis colomai (Lynch and Duellman, 1997) (Anura, Craugastoridae) - Valencia-Zuleta, Alejandro; Jaramillo-Martínez, Andrés Felipe; Yánez-Muñoz, Mario H. (Zootaxa, 2016)
We redescribe Pristimantis colomai (Lynch & Duellman, 1997) on the basis of new specimens from Colombia and Ecuador. Also provide a new diagnosis, reassess its distribution, and describe the mating call for the first time. Besides the data in the original description, only is available for this species: (i) new records from Ecuador (Yánez-Muñoz et al. 2011) and (ii) molecular phylogenetic inferences that place this species in the Pristimantis ridens series (Hedges et al. 2008; Padial et al. 2014). Pristimantis colomai is currently classified as endangered due to its restrict distribution and habitat quality (Castro et al. 2004).